Fuzhenghuayu decoction ameliorates hepatic fibrosis by attenuating experimental sinusoidal capillarization and liver angiogenesis - Liu, Hong-liang; Lv, Jing; Zhao, Zhi-min; Xiong, An-ming; Tan, Ye; Glenn, Jeffrey S.; Tao, Yan-yan; Weng, Honglei; Liu, Cheng-hai (Scientific reports, 2019)
Fuzhenghuayu (FZHY) is a compound extracted from natural plants. Its anti-fibrotic effect has been confirmed in experimental and clinical studies. However, precise effects and underlying mechanisms of FZHY in liver angiogenesis largely remain understood. In this study, we investigated the effects of FZHY on sinusoidal capillarization and angiogenesis with mice challenged for Carbon tetrachloride (CCl4) and dimethylnitrosamine (DMN), in vitro human hepatic sinusoidal endothelial cells (HHSEC) and Human Umbilical Vein Endothelial Cell (HUVEC) 3D fibrin gel model. Besides its anti-fibrotic effect, FZHY ameliorated CCl4 and DMN-induced sinusoidal capillarization, angiogenesis and expression of angiogenesis-associated factors, i.e. CD31, VEGF, VEGF receptor II, phosphor-ERK and HIF-1α. Consistent with the findings based on animal models, inhibitory effects of FZHY on capillarization and angiogenesis were further confirmed in HHSEC and the HUVEC 3D fibrin gel model, respectively. These data suggest that FZHY ameliorates not only liver fibrosis but also vessel remodeling in experimental models. Therefore, FZHY might be a potentially useful drug to treat liver cirrhosis in clinical practice.
Gesehen am 20.02.2020